Coronary Artery Disease–Associated and Longevity-Associated Polygenic Risk Scores for Prediction of Coronary Artery Disease Events in Persons Living With Human Immunodeficiency Virus: The Swiss HIV Cohort Study. (6th June 2021) - Schoepf, Isabella C; Thorball, Christian W; Ledergerber, Bruno; Engel, Tanja; Raffenberg, Marieke; Kootstra, Neeltje A; Reiss, Peter; Hasse, Barbara; Marzolini, Catia; Thurnheer, Christine; Seneghini, Marco; Bernasconi, Enos; et al.
Abstract: Background: Coronary artery disease (CAD) is in part genetically determined. Aging is accentuated in people with human immunodeficiency virus (HIV) (PLWH). It is unknown whether genetic CAD event prediction in PLWH is improved by applying individual polygenic risk scores (PRSs) and by considering genetic variants associated with successful aging and longevity. Methods: In the Swiss HIV Cohort Study participants of self-reported European descent, we determined univariable and multivariable odds ratios (ORs) for CAD events, based on traditional CAD risk factors, adverse antiretroviral exposures, and different validated genome-wide PRSs. PRSs were built from CAD-associated single-nucleotide polymorphisms (SNPs), longevity-associated SNPs, or both. Results: We included 269 patients with CAD events between 2000 and 2017 (median age, 54 years; 87% male; 82% with suppressed HIV RNA) and 567 event-free controls. Clinical (ie, traditional and HIV-related) risk factors and PRSs, built from CAD-associated SNPs, longevity-associated SNPs, or both, each contributed independently to CAD events ( P  < .001). Participants with the most unfavorable clinical risk factor profile (top quintile) had an adjusted CAD-OR of 17.82 (95% confidence interval [CI], 8.19–38.76), compared with participants in the bottom quintile. Participants with the most unfavorable CAD-PRSs (top quintile) had an adjusted CAD-OR of 3.17 (95% CI, 1.74–5.79), compared with the bottom quintile. After adding longevity-associated SNPs to the CAD-PRS, participants with the most unfavorable genetic background (top quintile) had an adjusted CAD-OR of 3.67 (95% CI, 2.00–6.73), compared with the bottom quintile. Conclusions: In Swiss PLWH, CAD prediction based on traditional and HIV-related risk factors was superior to genetic CAD prediction based on longevity- and CAD-associated PRS. Combining traditional, HIV-related, and genetic risk factors provided the most powerful CAD prediction. Abstract : Genetic background is associated with coronary artery disease (CAD) events. People living with human immunodeficiency virus have accentuated aging. Adding longevity-associated genetic variants to an individual polygenic risk score based on CAD-associated variants improves prediction of CAD events.